WiFi‐controlled portable atomic force microscope. Issue 9 (23rd May 2019) - Wang, Yingda; You, Qingyang; Zhang, Ziyao; Chen, Jiajun; Zhang, Haijun
Abstract: This article proposes to develop a WiFi‐controlled portable atomic force microscope (AFM). The AFM consists of a horizontal probe, controlling circuits, digital to analog (D/A) and analog to digital (A/D) interfaces, a microcomputer (Raspberry Pi, RPi), and a laptop. The proposed AFM uses a pocket‐size power supply to drive the controlling circuits, the D/A and A/D interfaces, as well as the RPi that constructs network hotspots and generates scanning signals. With special design and integration of the whole system, both of the AFM probe and electronic controlling system are portable. At a distance of 50 m from the proposed AFM, experiments in the constant height mode and the constant force mode are conducted to evaluate its performance. The results show that this WiFi‐controlled AFM has a maximum scan range of 3.6 × 3.6 μm 2 with nanometer order resolution. Meanwhile, it achieves satisfactory image contrast, stability, and repeatability. Compared with conventional AFMs, the AFM proposed in this paper no longer relies on commercial AC mains supply or high‐voltage DC power supply, and realizes WiFi‐controlled AFM scanning and imaging in 50 m or farther without wire or network cable connection to a laptop or a desktop computer. Given credits to these features, WiFi‐controlled AFMs are expected to own a wider range of application, especially in isolated environments, outdoor researches, or even fieldwork investigations. Abstract : This article proposes a specially designed/constructed portable atomic force microscope (AFM) capable of achieving WiFi‐controlled imaging of nano‐structured samples. The AFM can be used both indoors and outdoors, especially in fieldwork researches.